Several Enantiopure Chiral Building Blocks Derived from D‐Mannose and a Formal Synthesis of Dubiusamine C. Issue 7 (23rd March 2016) - Tan, Dongxing; Xu, Murong; Xu, Zejun; Wu, Yikang; You, Jun
Abstract: Several multi‐functional chiral building blocks derived from D ‐mannose are developed, which may find diverse utilities as sources of 1‐hydroxy‐3‐methyl structural units in enantioselective synthesis of many natural products. A formal synthesis of natural dubiusamine‐C is also presented. Abstract : All these bi‐/multi‐functional small molecules contain a configurationally well‐defined 1‐hydroxy‐3‐methyl structural unit, with different reacting sites at the chain terminals ready for different applications.